The Effectiveness of Repetitive Transcranial Magnetic Stimulation for Post-stroke Dysphagia: A Systematic Review and Meta-Analysis - Wen, Xin; Liu, Zicai; Zhong, Lida; Peng, Yang; Wang, Jing; Liu, Huiyu; Gong, Xiaoqian (Frontiers in Human Neuroscience, 2022)
Background Repetitive transcranial magnetic stimulation (rTMS) applied to the mylohyoid cortical region has positive clinical effects on post-stroke. Therefore, we conducted a meta-analysis to investigate the efficacy of rTMS for patients with post-stroke dysphagia. Methods According to PRISMA guidelines, we searched the databases of MEDLINE (PubMed), Cochrane Library, Embase, Web of Science, CNKI, Wangfang. We searched for studies of randomized controlled trials (RCTs) of rTMS to treat dysphagia after stroke and screened by inclusion and exclusion criteria. Features of RCTs were extracted. The heterogeneity of the trials was measured by I2 statistic. Results In total, 11 RCTs with 463 dysphagia patients fulfilled our inclusion criteria. In our analysis, rTMS demonstrated a great beneficial effect for post-stroke dysphagia when combined with traditional swallowing exercises. Moreover, a greatly significant difference (P = 0.008) was noted based on stimulation frequency (high frequency vs. low frequency). Additionally, no significant difference (P = 0.53) was observed based on stimulation site (affected vs. unaffected hemisphere). Conclusions Overall, rTMS can effectively accelerate the improvement of swallowing function in patients with post-stroke swallowing disorders.